Glacial Striae and Crescentic Marks in Nepean Sandstone near Ottawa - Hill, Patrick; Billings, Dennis (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1985)
Summary An outcrop of Nepean Sandstone (Cambro-Ordovician) at Kanata, 21 km west of Ottawa, containing a unique concentration, diversity and distribution of glacial striae and crescentic markings has been partly removed by highway construction, leaving the north sloping stoss end and part of the top surface. Two sets of striae are preserved. The main set, indicating iceflow toward the south-southwest across the Ottawa Valley, is transected by short, deep, west-east striations indicating a late and final ice flow downvalley to the east. East-trending striations are seldom observed in the Ottawa Valley. Crescentic markings variously termed gouges, scours, scars, or pluckings, are on the northern stoss slope, concave up-ice toward the north. On average, these are 25cm across, about 5 cm broad and 1 to2.5 cm deep. They become progressively less crescentic and less concave away from the stoss slope and change to fine, hairline fractures on the more polished top surface, becoming convex up-ice toward the southern end of the outcrop. The change in crescentic form from north to south along the outcrop clearly represents a differential impingement of ice and its contained boulders over the surface of the outcrop.